D' Sajla - Mohd Badrul, Nurdiana Syahira; Fadzle, Fareen Nuralisa; Zulkipli, Nurfithriah; Mohd Ghazali, Nur Aliah; Azaman, Nurul Anis Afiqa; Omar, Afiqah Hanani; Amir Hamzah, Nur Asyiqin (2015)
D' Sajla is a Small Medium Industry (SMI) company whose main product is the sale of praying mats. The company's strategy is to identify and target areas with high demand through surveys, personal observation, and interviews. D' Sajla aims to attract customers by offering creative and innovative designs, making the modification of the praying mat a central competitive strategy. A key objective and priority for the company is providing excellent customer service, which includes maintaining good customer relations through continuous communication and receiving feedback. The company is composed of seven members, each possessing specialized skills in various fields, such as accounting, human resources, and marketing. D' Sajla believes that the team's talent and creativity, coupled with teamwork, discussion, and commitment, are the essential keys to achieving the company's goals and overall success.